2015
DOI: 10.1590/0103-166x2015000200010
|View full text |Cite
|
Sign up to set email alerts
|

Work-related values and organizational values from the perspective of university professors: A correlational study

Abstract: The alignment of personal and organizational values can positively influence performance. Considering the motivational aspect of these values, organizations and workers seek to satisfy their goals and needs through work. Thus, the study of personal and organizational values of university professors can contribute to the production of science, technology and innovation through committed professionals with this strategic axis. The aim of the present study was to evaluate work-related values and their relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…With that, Camara and Pereira-Guizzo (2015) [11] concluded that positive social relationships stimulate innovation. From there, the hypothesis is posited as follows:…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
“…With that, Camara and Pereira-Guizzo (2015) [11] concluded that positive social relationships stimulate innovation. From there, the hypothesis is posited as follows:…”
Section: Research Hypothesis and Modelmentioning
confidence: 99%
“…Relaciones Sociales presentó correlación con los valores organizacionales de Autonomía (p = 0,018), Realización (p = 0,001), Dominio (p = 0,048), Prestigio (p = 0,001), Cumplimiento (p = 0,016) y la Responsabilidad Social (p = 0,014). Estos resultados sugieren la importancia de los valores para la satisfacción en el trabajo y el desarrollo de estrategias organizacionales (Câmara, et al 2015).…”
Section: Diferencias Entre Los Componentes Del Capital Psicológicounclassified
“…A universidade pública no Brasil emprega funcionários administrativos que, em alguns casos de maior nível funcional, possuem autonomia para tomar decisões no dia-a-dia e se auto organizam para cumprir com os objetivos da universidade (CÂMARA e PEREIRA- GUIZZO, 2015). 1 Tomando-se esta abordagem como ponto de partida, propõe-se nesta dissertação observar como se desenvolvem a aprendizagem e a capacitação de funcionários públicos.…”
Section: Introductionunclassified